Introduction to Transcriptomics - Ahmad, Umar Salisu (My University, 2021)
Slide deck for a presentation on transcriptomics, delivered on 25.06.2021 during a training session entitled 'Beginner's Guide to Bioinformatics,' organized by Helix Biogen Institute in Nigeria.
Keywords: Transcriptomics; Diseases; Biomarkers